Research on the Current Situation, Problems, and Countermeasures of Traditional Chinese Opera Education Curriculum Development - Deng, Qinfang; Lee, Seungjin (Journal of Educational Research and Policies, 2025)
Traditional Chinese opera education, as an essential part of China’s outstanding traditional culture, plays a crucial role in both arts’ education and cultural heritage. In recent years, the government has introduced a series of policies to support the development of traditional opera education. However, challenges such as an underdeveloped curriculum system, a shortage of qualified teachers, limited teaching methods, and low student interest persist in practice. This paper analyzes the current state of traditional opera education from the perspectives of policy background, curriculum development, teaching methods, and evaluation systems. It explores the key issues and proposes countermeasures, including optimizing curriculum objectives, enriching teaching resources, enhancing teachers’ professional competencies, innovating teaching approaches, and improving evaluation mechanisms. These strategies aim to promote the sustainable development of traditional opera education and provide valuable insights for the future construction of traditional opera education curricula.